Pengembangan Aplikasi Pencarian Tutor Les Privat Berbasis Mobile Menggunakan Metode Profile Matching - Dapamudang, Milton; Alfrian C Talakua (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Education is vital for human beings to develop and continue their lives. Although many of the tutor search apps are available, students in Eastern Sumba have difficulty enjoying this service because no private tutor is resident in East Sumba. A private lesson tutor is important for students who need more intensive learning outside of school, especially parents who are busy or do not have the opportunity or knowledge to help their children. The challenge often faced is the difficulty of finding a tutor that suits the needs of the student. The use of profile matching methods can help parents or student guardians find private tutors based on specific needs or preferences, such as subject, level of experience, location, or other criteria. Tutors that meet these criteria will appear as search results. Testing with the System Usability Scale (SUS) showed that the application is qualified for users, as it achieved an average score of 72.62.